#### Answer

The function is even.

#### Work Step by Step

We have that $E(-x)=E(x)$ and $O(-x)=-O(x)$.
Let $\Phi=E\circ E$. Then
$$\Phi(-x)=E\circ E(-x)=E(E(-x))=E(E(x))=E\circ E(x)=\Phi(x)$$
which means that the function is even.

Published by
Pearson

ISBN 10:
0321947347

ISBN 13:
978-0-32194-734-5

The function is even.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.